Knowledge management for ERP implementation - Rong, Kong (2007)
We are living in knowledge world nowadays. So people need to seek knowledge from born until death and many enterprises consider knowledge as their invisible asset. Knowledge Management becomes a hot topic for researchers. Enterprise Resource Planning is a type of knowledge which published by research and analysis firm Gartner Group in 1990. Successful implementation of ERP is not easy like somebody’s thinking because ERP is not a simple system to implement and it consists of many parts such as tangible assets, financial resources, materials, and human resources. In fact, failure of ERP implementation is higher. The ERP implementation research is in a relatively new area although many enterprises started implement ERP system. In recent years, some research institutes and ERP system companies are looking for suitable implementation method which can effectively increase successful rate of ERP implementation. This thesis focuses on Knowledge Management and ERP implementation and tries to use Knowledge Management do a better ERP implementation.